Complications, comorbidities and quality of life after duodenal switch operation at Nordland hospital 2006-2010. - Slettvold, Vegard Daniel (UiT Norges arktiske universitet, 2016)
ABSTRACT Project aims and objectives We investigated the duodenal switch procedure performed at Nordland hospital in the period 2006 – 2010. Weight and comorbidities before and after surgery, complications, re-operations, department learning curve and quality of life after surgery were assessed. Introduction Obesity is an increasing health problem worldwide and it is associated with serious comorbidities such as diabetes mellitus type II, hypertension and obstructive sleep apnea. Treatment options include lifestyle intervention, medications and bariatric surgery. Duodenal switch is one of the bariatric surgery procedures in use today, it results in weight loss and reduction in comorbidities, but carries risks of complications. Material and methods 41 patients were enrolled in this retrospective study. Data were collected searching the electronic health record DIPS, and quality of life scores were collected through a questionnaire. All data were analyzed using SPSS for Mac IOS. Results Mean weight loss 1 year after surgery was 72,6 kg. At last control after surgery comorbidity rates were reduced from 36,6% to 0% for diabetes, from 43,9% to 12,2% for hypertension and from 46,3% to 4,9% for OSAS. 24,4% suffered an early complication. 39% suffered a late complication. 26,8% was re-operated. Mean quality of life score was 3 out of maximum 4. No learning curve for the department was observed. Discussion and conclusion Duodenal switch procedure for obesity seems to be a highly effective treatment resulting in substantial weight loss and a nearly resolution of comorbidities one year after surgery. At last control (in average 44 months after surgery) these results were stable. The procedure for this group of patients probably carries a high risk of early and late complications, re-operations, iron- and vitamin D-deficiency and need for plastic surgery.